Ongoing Pregnancies following Cosmetic Micromanipulation of Preimplantation Embryos in Patients with Implantation Failure. (13th October 2015) - Halvaei, Iman; Khalili, Mohammad Ali; Safari, Somayyeh; Esfandiari, Navid
Abstract : Cosmetic micromanipulation is defined as fragment and coarse granulation removal from preimplantation embryos. We report two cases of pregnancies in patients with implantation failure following cosmetic micromanipulation.